1982
DOI: 10.1007/bf00431943
|View full text |Cite
|
Sign up to set email alerts
|

The active uptake of serotonin by platelets of schizophrenic patients and their families: Possibility of a genetic marker

Abstract: The active uptake of serotonin (5-HT) blood platelets of 20 schizophrenic patients and their families was studied. The uptake was studied over a wide range of 5-HT concentrations (0.1-20 microM), and Km and Vmax of the uptake process were calculated. Of 20 patients, 18 exhibited a lower rate of uptake than the family average at 5-HT concentrations lower than the Km value. At a 5-HT concentration of 0.1 microM, the average 5-HT uptake of patients was 2.15 pmol/10(8) platelets/min, while that of families was 2.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1983
1983
1988
1988

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…These sites appear to be specific for tricyclic antidepressants and their active metabolites (Langer et al 1981), and appear to have a functional relationship with the 5HT uptake or transport site, probably modulating inhibition of 5HT uptake (Paul et al 1980). While Rotman et al (1982 b ) reported decreased 3 H-imipramine binding and 5HT uptake in platelets of schizophrenic patients, Wood et al (1983), Gentsch et al (1985), Weizman et al (1985), Weizman et al (1987), and Kanof et al (1987) could not find any significant difference in 3 H-imipramine binding between schizophrenic and normal control subjects. Thus, it seems likely that the 3 H-imipramine binding site is intact in schizophrenia.…”
Section: Platelet Studiesmentioning
confidence: 90%
See 3 more Smart Citations
“…These sites appear to be specific for tricyclic antidepressants and their active metabolites (Langer et al 1981), and appear to have a functional relationship with the 5HT uptake or transport site, probably modulating inhibition of 5HT uptake (Paul et al 1980). While Rotman et al (1982 b ) reported decreased 3 H-imipramine binding and 5HT uptake in platelets of schizophrenic patients, Wood et al (1983), Gentsch et al (1985), Weizman et al (1985), Weizman et al (1987), and Kanof et al (1987) could not find any significant difference in 3 H-imipramine binding between schizophrenic and normal control subjects. Thus, it seems likely that the 3 H-imipramine binding site is intact in schizophrenia.…”
Section: Platelet Studiesmentioning
confidence: 90%
“…A number of studies conducted by Rotman's group (Modai et al 1979;Rotman et al 1979Rotman et al , 1980Rotman et al , 1982a have shown that 5HT uptake in platelets of schizophrenic patients is significantly reduced in comparison to normal controls. This finding was related High in schizophrenic patients with cortical atrophy or ventricular enlargement High in schizophrenic patients, particularly with chronic undifferentiated subtype High in schizophrenic patients, particularly correlated with auditory hallucinations High in schizophrenic patients High in schizophrenic patients, particularly correlated with cerebrospinal fluid 5hydroxyindoleacetic acid and abnormal motor behavior 62 'NS = no significant differences between groups.…”
Section: Platelet and Whole Blood 5htmentioning
confidence: 99%
See 2 more Smart Citations
“…Codd often interact, thus increasing the complexity of their influence. For example, intrinsic factors such as sex (Wirz-Justice and Chappuis-Arndt 1976;Guicheney and Marcel 1984) and genetic variability (Rotman et al 1982;Arora et al 1983;Codd and Walker 1987) may influence platelet 5 HT uptake differentially, depending upon their interactions with extrinsic factors such as time of day (Oxenkrug et al 1978;Humphries et al 1985; Modai et all. 1986), season (Wirz-Justice etal.…”
mentioning
confidence: 99%